Evaluation of multipurpose tree germplasm: The use of gas production and rumen degradation characteristics - Siaw, D.E.K.A.; Osuji, P.O.; Nsahlai, I.V. (Cambridge University Press, 1993)
The rumen degradation and gas production characteristics (methane, carbondioxide) of leaves of 20 accessions of multipurpose trees (MPTs) from six genera: Acacia, Cajanus, Chamaecytisus Link, Erythrina, Leaucaena and Sesbania and some poisonous plants were investigated in vitro and in sacco in rumen fistulated cows fed on a diet of grass hay ad libitum supplemented with cotton seed cake. The degradation constants were calculated. The gas production constants were estimated. Between and within genus comparisons of degradability and gas production constants were done. The soluble fraction was significantly higher for Sesbania than the other genera. There was no significant differences in the slowly degradable fraction between genera. Sesbania was degraded significantly faster than either Acacia, Leucaena or Cajanus. The potential degradability was also significantly higher for Sesbania. Acacia was the least degradable genus. Degradation characteristics were similar between species within the genera Acacia, Erythrina and Leucaena. However, within the Leucaena genus, L. revoluta had the highest soluble fraction and the cross L. leucocephala X L. diversifolia had the lowest. L. leucocephala had the highest slowly degradable fraction and L. revoluta had the lowest. L. leucocephala X L. pallida had the highest potential degradability and the cross L. pallida X L. diversifolia the lowest. Between the genera, more gas was produced from Sesbania than from any other genus. The effect of genus was significant. On the other hand, the rate of gas produciton was higher with the genus Chamaecytisus than with any other genera. Although the two methods used agree in the position of a forage of a high degradability like Sesbania, they fail to agree on the relative positions of the forages of lower degradabilities. For some genera, drying of the tree foliage reduced the volume of gas produced, but increased the rate of gas production.